Depositional evolution of a progradational to aggradational, mixed-influenced deltaic succession: Jurassic Tofte and Ile formations, southern Halten Terrace, offshore Norway. (February 2017) - van Cappelle, Marijn; Ravnås, Rodmar; Hampson, Gary J.; Johnson, Howard D.
Abstract: Predicting the hydrodynamics, morphology and evolution of ancient deltaic successions requires the evaluation of the three-dimensional depositional process regime based on sedimentary facies analysis. This has been applied to a core-based subsurface facies analysis of a mixed-energy, clastic coastal-deltaic succession in the Lower-to-Middle Jurassic of the Halten Terrace, offshore mid-Norway. Three genetically related successions with a total thickness of 100–300 m and a total duration of 12.5 Myr comprising eight facies associations record two initial progradational phases and a final aggradational phase. The progradational phases (I and II) consist of coarsening upward successions that pass from prodelta and offshore mudstones (FA1), through delta front and mouth bar sandstones (FA2) and into erosionally based fluvial- (FA3) and marine-influenced (FA4) channel fills. The two progradational phases are interpreted as fluvial- and wave-dominated, tide-influenced deltas. The aggradational phase (III) consists of distributary channel fills (FA3 and FA4), tide-dominated channels (FA5), intertidal to subtidal heterolithic fine-grained sandstones (FA6) and coals (FA7). The aggradational phase displays more complex facies relationships and a wider range of environments, including (1) mixed tide- and fluvial-dominated, wave-influenced deltas, (2) non-deltaic shorelines (tidal channels, tidal flats and vegetated swamps), and (3) lower shoreface deposits (FA8). The progradational to aggradational evolution of this coastal succession is represented by an overall upward decrease in grain size, decrease in fluvial influence and increase in tidal influence. This evolution is attributed to an allogenic increase in the rate of accommodation space generation relative to sediment supply due to tectonic activity of the rift basin. In addition, during progradation, there was also an autogenic increase in sediment storage on the coastal plain, resulting in a gradual autoretreat of the depositional system. This is manifested in the subsequent aggradation of the system, when coarse-grained sandstones were trapped in proximal locations, while only finer grained sediment reached the coastline, where it was readily reworked by tidal and wave processes. Graphical abstract: Highlights: Core-based sedimentology of Jurassic deltaic strata from offshore Norway. Facies analysis of tide-influenced deltaic and estuarine petroleum reservoirs. Temporal development of deltaic deposits fed from multiple sediment sources. Temporal development of tide-influenced deltaic deposits in a rift basin. Synthesis of allocyclic and autocyclic processes on stratigraphic architecture.